Humanização do divino, divinização do humano: representações do imaginário religioso no teatro de Ariano Suassuna - Pimentel, Claudio Santana (2010)
This dissertation analysis the theatrical works of Ariano Suassuna; focusing reinterpretations and re-significations from the popular religious imagery, to understand how religious representations allow the development of identity and meaning forms. For both, we based in an interdisciplinary analytical instrument own researches on Religious Studies. Initially, we investigated the author's assumptions about the relationship between art and religion, then to discuss his conception of the world and humanity. These ideas form the basis on which the author develops his religious vision. Considering this, we discussed the importance of the categories of tragedy and comedy to the development of religious themes by Suassuna. We conclude that the redefinition of religious elements in the theatrical works of Suassuna explains the continuing efforts of humans to develop a meaning for life, from a dialogue between local and universal. We also believe that such representations provide elements for better understanding of the Brazilian religious imagery, even in this urban context